2010
DOI: 10.1186/1532-429x-12-65
|View full text |Cite
|
Sign up to set email alerts
|

Reference left atrial dimensions and volumes by steady state free precession cardiovascular magnetic resonance

Abstract: BackgroundLeft atrial (LA) size is related to cardiovascular morbidity and mortality. Cardiovascular magnetic resonance (CMR) provides high quality images of the left atrium with high temporal resolution steady state free precession (SSFP) cine sequences. We used SSFP cines to define normal ranges for LA volumes and dimensions relative to gender, age and body surface area (BSA), and examine the relative value of 2D atrial imaging techniques in patients.For definition of normal ranges of LA volume we studied 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
206
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(221 citation statements)
references
References 44 publications
13
206
1
1
Order By: Relevance
“…Hudsmith et al [6,21] also reported higher absolute LA volumes in male patients with similar ejection fraction in patients of both genders. Regarding indexed LA volumes, our findings are broadly consistent with those reported by Maceira et al [4]. The effect of age may explain the greater indexed LA maximum volumes observed in men.…”
Section: Gender Differences In Left Atrial Measuressupporting
confidence: 82%
See 1 more Smart Citation
“…Hudsmith et al [6,21] also reported higher absolute LA volumes in male patients with similar ejection fraction in patients of both genders. Regarding indexed LA volumes, our findings are broadly consistent with those reported by Maceira et al [4]. The effect of age may explain the greater indexed LA maximum volumes observed in men.…”
Section: Gender Differences In Left Atrial Measuressupporting
confidence: 82%
“…Several studies have defined CMR normal ranges of LV volumes and systolic function [4][5][6][7][8][9][10][11] but none has assessed the prevalence of left ventricular diastolic dysfunction in healthy adult individuals.…”
Section: Introductionmentioning
confidence: 99%
“…329,331,[333][334][335][336][337][338][339]345,[347][348][349][350][351][352][353][354][355][356][357][358][359][360] Two-dimensional echocardiographic LA volumes are typically smaller than those reported from computed tomography or cardiac magnetic resonance imaging (CMR). [361][362][363][364][365] Left atrium volume from 2D images is best measured using the disk summation algorithm because it includes fewer geometric assumptions. 366,367 The advent of 3-D ECHO has improved the accuracy of ECHO volume measurements which correlate well with cardiac computed tomography 368,369 and magnetic resonance imaging.…”
Section: Echocardiographymentioning
confidence: 99%
“…This form of scaling may be useful in a normal population where atrial volumes vary with BSA (11). However, in an athletic population the atrial volumes are also increased due to training and therefore all volumes normalized for BSA will be higher and often above the limits of normal remodeling (6).…”
Section: Introductionmentioning
confidence: 99%
“…Cut off values for normal atrial remodeling are often presented normalized for body surface area (BSA) (8)(9)(10)(11)(12). This form of scaling may be useful in a normal population where atrial volumes vary with BSA (11).…”
Section: Introductionmentioning
confidence: 99%